Literature Review: Penggunaan Komik dalam Pembelajaran Bahasa Asing untuk Pengembangan Media Ajar Bahasa Jepang Berfokus pada Bentuk dan Tampilan Komik - Via Luviana Dewanty; Dewi Kusrini; Renindra Atsilah Putri (Universitas Negeri Semarang, 2022)
The study was aimed to discover the form of comics used in language learning and the development process, as well as the style of the Comic suitable with the interest of Japanese language students used in the previous study, which is expected to elaborate types of necessary research in the future for Japanese language teaching material development. There were 20 articles reviewed related to comics development for language learning. Based on the review result, it was found that 1) There are two types of comics, namely 1-Panel Comic used to explain one specific material and 4-Panel Comic used for conversation materials. However, there has yet any research related to comics development in the form of comic books; 2) In terms of process, both types of comics are formulated and developed by referring to a curriculum and learning plan so that the comics may assist students in understanding learning material; 3) Comic styles discussed in previous researches refer to American comic style, and thus less suitable to be used as Japanese language learning materials. The style used in Japanese comics is predicted to be more attractive for Japanese language students. However, there has yet any scientific study on the development of Japanese style comics in Japanese language learning.